Field programmable gate array hardware in the loop validation of fuzzy direct torque control for induction machine drive - Aib, A.; Khodja, D. E.; Chakroune, S. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Currently, the direct torque control is very popular in industry and is of great interest to scientists in the variable speed drive of asynchronous machines. This technique provides decoupling between torque control and flux without the need to use pulse width modulation or coordinate transformation. Nevertheless, this command presents two major importunities: the switching frequency is highly variable on the one hand, and on the other hand, the amplitude of the torque and stator flux ripples remain poorly controlled throughout the considered operating speed range. The novelty of this article proposes improvements in performance of direct torque control of asynchronous machines by development of a fuzzy direct torque control algorithm. This latter makes it possible to provide solutions to the major problems of this control technique, namely: torque ripples, flux ripples, and failure to control switching frequency. Purpose. The emergence of this method has given rise to various works whose objective is to show its performance, or to provide solutions to its limitations. Indeed, this work consists in validation of a fuzzy direct torque control architecture implemented on the ML402 development kit (based on the Xilinx Virtex-4 type field programmable gate array circuit), through hardware description language (VHDL) and Xilinx generator system. The obtained results showed the robustness of the control and sensorless in front of load and parameters variation of induction motor control. The research directions of the model were determined for the subsequent implementation of results with simulation samples.

В даний час пряме управління моментом дуже популярне в промисловості і викликає великий інтерес у вчених у галузі частотно-регульованого приводу асинхронних машин. Цей метод забезпечує розв'язку між керуванням моментом, що крутить, і магнітним потоком без необхідності використання широтно-імпульсної модуляції або перетворення координат. Тим не менш, ця команда представляє дві основні незручності: з одного боку, частота комутації сильно варіюється, а з іншого боку, амплітуда пульсацій моменту і потоку статора залишається погано контрольованою у всьому діапазоні робочих швидкостей. Новизна цієї статті пропонує поліпшення характеристик прямого керування моментом, що крутить, асинхронних машин шляхом розробки нечіткого алгоритму прямого управління моментом, що крутить. Останнє дозволяє вирішити основні проблеми цього методу управління, а саме: пульсації моменту, що крутить, пульсації потоку і нездатність контролювати частоту перемикання. Мета. Поява цього методу породило різні роботи, метою яких є показати його ефективність чи запропонувати рішення стосовно його обмежень. Дійсно, ця робота полягає у перевірці нечіткої архітектури прямого управління моментом, що крутить, реалізованої в наборі для розробки ML402 (на основі схеми Xilinx Virtex-4 з програмованою користувачем вентильною матрицею), за допомогою мови опису обладнання (VHDL) та генераторної системи Xilinx. Отримані результати показали робастність керування та безсенсорного керування при зміні навантаження та параметрів керування асинхронним двигуном. Визначено напрями дослідження моделі для подальшої реалізації результатів на імітаційних вибірках.
Keywords: fuzzy control; field programmable gate array; Xilinx system generator; direct torque control; power system; нечітке управління; програмована користувачем вентильна матриця; генераторна система Xilinx; пряме управління моментом, що крутить; система живлення